Managerial decision cases - Finnegan, Thomas (Australia ; United Kingdom : South-Western College ; Thomson Learning, 2001)
Introduction. Basic concepts. Activity cost behavior. Activity-based costing (ABC). ABC and ABM. Job order costing. Process costing. Cost allocation. Budgeting. Variance analysis...
Keywords: Management; Decision making; Decision making -- Case studies; Decision making